How does top management team composition matter for continual growth? Reinvestigating Penrose's growth theory through the lens of upper echelons theory. Issue 1 (25th June 2018) - Chen, Wein-Hong; Kang, Min-Ping; Butler, Bella
Abstract : Purpose: Penrose's argument regarding the managerial constraint on continual expansion over two consecutive periods is termed the "Penrose effect, " a relatively less investigated premise in Penrose's growth theory. The purpose of this paper is to empirically re-examine the Penrose effect from the perspective of upper echelons theory and investigated how top management team (TMT) composition influences the continual growth of a firm. Design/methodology/approach: This study empirically tested the hypotheses based on a sample of listed manufacturing firms operating in Taiwan, a newly industrialized economy in the Asia–Pacific region. Moderated hierarchical regression analyses were applied to test hypotheses. Findings: The empirical results suggest that low TMT diversity (in terms of educational, functional and team tenure diversity) is likely to engender a situation in which the Penrose effect might occur. Additionally, the results indicate that the proportion of functional executives plays a significant role in influencing the growth trend over two consecutive periods and may soften the impact of the Penrose effect. Practical implications: This paper suggests that appropriate structuring of TMTs and appropriate management of their members' backgrounds and team tenure diversity can help firms overcome the Penrose effect and grow continually. Furthermore, the proportion of functional executives in a TMT is influential. Originality/value: This paper uniquely contributes to the theoretical and empirical development of Penrose's growth theory, upper echelons theory and resource-based view concerning managerial resources.